(untitled) (One Health & Risk Management, 2023)
THE PROFESSIONAL RISKS OF HEALTHCARE WORKERS Aim. In this study, an attempt was made to identify the problems, causes, risk factors that condition the occurrence of occupational morbidity and remedial measures for the health problems of medical workers. Material and methods. A cross-sectional epidemiological study involving 120 healthcare workers was designed. The questionnaire was administered online using the Google Forms platform between January and June 2022. Descriptive analysis of the study was conducted, calculating absolute frequencies and percentage ratios to provide a comprehensive overview of the data. Results. The sample under investigation comprised 120 medical workers, with respondents’ ages ranging from 18 to 71 years and an average age of 47.1±14.94 years (M±SD). Medical professionals encounter various occupational risks, including psychosocial factors, high workload, neuro-emotional and physical demands, and incidents of violence. The most prevalent workplace situations reported by the respondents were dialogue with patients (57.5%), an overburdened work regime (57.5%), intercollegiate relations (41.7%), boss-subordinate relationships (34.2%), and 12.5% reported encountering none of these situations. Conclusions. The professional activities of medical workers are associated with significant health risk factors. To enhance working conditions and mitigate morbidity resulting from the occupational environment, it is essential to address organizational issues. This includes ensuring compliance with the work and rest regime, promoting rational nutrition, reducing risk factors, and establishing optimal working conditions.